Biodiversity Risk, Audit Pricing, and the Institutionalization of Ecological Risk - Deng, Beier (Journal of Cultural Analysis and Social Change, 2026)
This study examines the influence of enterprise-level biodiversity risk monitoring indicators on audit fees using a sample of Chinese A-share listed businesses from 2016 to 2021. The research finds that biodiversity risk is significantly positively correlated with audit fees. The reasons mainly include two aspects: first, verifying complex biological assets and compliance with environmental regulations requires increased audit investment; second, a risk premium needs to be charged for potential lawsuits and reputational losses related to environmental scandals. This research makes two principal contributions: first, it expands the research scope of the economic consequences of biodiversity. Second, it adds to the body of knowledge about the factors that influence audit fees.